Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2020
DOI: 10.2147/jir.s232157
|View full text |Cite
|
Sign up to set email alerts
|

<p>Higher Dietary Inflammatory Index Scores are Associated with Increased Odds of Benign Breast Diseases in a Case–Control Study</p>

Abstract: Purpose: Dietary inflammatory index (DII) is a new tool for assessing the inflammatory potential of diet. Since there is no study that has investigated the association of DII and benign breast diseases (BBD), the aim of our study was to compare DII scores in patients with and without BBD. Methods: One hundred and eleven (111) subjects with BBD and 104 healthy women attending the Iranian Center for Breast Cancer affiliated with the Academic Center for Education, Culture and Research were enrolled in a case-cont… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 54 publications
0
4
0
Order By: Relevance
“…Dietary intake of MUFAs was only positively related to DII and not E-DII. In a study by Aghababayan et al, only dietary intakes of total fat, cholesterol, and SFA were significantly higher in the upper tertile of DII (58). In another study, dietary intakes of carbohydrates, fibers, and PUFAs were higher in the lowest tertile of DII; however, dietary intakes of cholesterol, SFAs, and MUFAs were higher in the third quartile of DII (59).…”
Section: Discussionmentioning
confidence: 86%
“…Dietary intake of MUFAs was only positively related to DII and not E-DII. In a study by Aghababayan et al, only dietary intakes of total fat, cholesterol, and SFA were significantly higher in the upper tertile of DII (58). In another study, dietary intakes of carbohydrates, fibers, and PUFAs were higher in the lowest tertile of DII; however, dietary intakes of cholesterol, SFAs, and MUFAs were higher in the third quartile of DII (59).…”
Section: Discussionmentioning
confidence: 86%
“…Boeke et al 32 disclosed a positive association with alcohol and a negative association between nuts and BBD. Aghababayan et al 33 approached the issue of nutrients and BBD from another perspective. In one study, 33 they calculated the dietary inflammatory index in the diets of patients and showed a probable direct association with using higher amounts of foods with inflammatory potential.…”
Section: Discussionmentioning
confidence: 99%
“…Aghababayan et al 33 approached the issue of nutrients and BBD from another perspective. In one study, 33 they calculated the dietary inflammatory index in the diets of patients and showed a probable direct association with using higher amounts of foods with inflammatory potential. In a second study, 34 they considered the dietary phytochemical index of the diets and showed an inverse association with BBD.…”
Section: Discussionmentioning
confidence: 99%
“…Accordingly, a subgroup analysis that only included the cohort studies revealed a more moderate association between the DII and breast cancer risk. Aside from the studies included in this meta-analysis, one previous study found no association between the DII and breast cancer-specific deaths [ 24 ], while Aghababayan et al [ 25 ] reported a possible association between the DII and benign breast tumors.…”
Section: Discussionmentioning
confidence: 99%